From Frankenstein foods to Veggie box schemes: Sustainable consumption in cultural perspective - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
Sustainable consumption (SC) and sustainable lifestyles have become prominent areas of environmental discourse and decision-making in recent years, and have been adopted as policy objectives by international agencies, national governments, local authorities, NGOs and citizen's action groups. The tools proposed for SC include eco-labelling, environmental taxation, green consumerism, regulation, downshifting, localisation etc., and these tools reflect the very different values and beliefs which are held by different actors in society, about what SC might be and how to achieve it. This paper examines the principal discourses of SC using a cultural theory analytical framework. It illustrates a range of perspectives of SC as being representative of underlying worldviews and beliefs about the environment and society. Using food as a case study, the issues and values surrounding SC are highlighted, referring to fair trade, local production and distribution (farmers markets, organic box schemes), GM foods and organics (local and imported). The analytical framework is used to explore the ways in which citizens' and community groups' efforts to enact SC at the local level and in everyday life, are shaped, helped or hindered by the embodied values of social institutions and higher levels of decision-making. The cultural theory framework itself is critically analysed, and found to be a useful heuristic tool for categorising different SC views and initiatives, but lacking in explanatory power when attention turns to structural power relations and the hegemony of individualistic market culture. The policy implications of this analysis are discussed: governments should intervene to create space for marginalised cultures and act to widen the real choices available to consumers and citizens.
Keywords: 330; cultural theory; environmental governance; Food; green consumerism; sustainable consumption; Nachhaltige Entwicklung; Umweltbewusstsein; Konsumentenverhalten; Biokost